Characterization of Mechanical Properties and Melt Flow Behavior of rPET from Waste Bank Sources Using Twin-Screw Extrusion - Meilani Manurung; Adhe Aryswan; Adi Syahputra Purba; Benny Hadli Irawana; Kholilur Rahman (SAINSTEK, 2026)
Polyethylene terephthalate (PET) is one of the most widely used thermoplastic polymers in packaging applications, contributing significantly to global plastic waste generation. Mechanical recycling of post-consumer PET (rPET) offers a practical solution to reduce environmental impact; however, the variability of feedstock obtained from decentralized waste collection systems, such as waste banks, poses challenges in ensuring consistent material performance. This study aims to characterize the mechanical properties and melt flow behavior of post-consumer rPET derived from waste bank sources and processed using twin-screw extrusion. PET bottle waste was collected, cleaned, and processed into pellets under controlled extrusion conditions. The resulting material was evaluated through melt flow index (MFI) tested at 270°C with an applied load of 2.16 kg in accordance with ASTM D1238, alongside tensile strength, hardness, and elongation at break tests. The results show that the recycled PET exhibits an average MFI of 60.8 g/10 min, tensile strength of 64.1 MPa, hardness of 84.9 Shore D, and elongation at break of 10.9%. The tensile strength falls within the range previously reported for mechanically recycled PET (48.3–72.4 MPa), while the low elongation at break reflects reduced ductility consistent with thermo-mechanical degradation. This study provides preliminary baseline data on the properties of rPET sourced from waste bank systems, offering foundational insights into its potential suitability for rigid secondary manufacturing applications where structural stability is prioritized over flexibility, pending broader validation with larger sample sizes and direct comparative testing against commercially recycled PET.